2019
DOI: 10.3389/fcell.2019.00224
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Assembly of Human Salivary Stem/Progenitor Microstructures Requires Coordinated α1β1 Integrin-Mediated Motility

Abstract: A tissue engineering approach can provide replacement salivary gland structures to patients with hyposalivation disorders and xerostomia. Salivary human stem/progenitor cells (hS/PCs) were isolated from healthy regions of parotid glands of head and neck surgery patients, expanded, then encapsulated in biocompatible hyaluronate (HA)-based hydrogels. These bioactive hydrogels provide a surrogate territorial matrix suitable for the dynamic assembly, growth and reorganization of salivary gland components. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Ki67 and PCNA proteins are markers of cell proliferation, and CK7 is the marker of salivary ductal cells, respectively. 27,28 In the non-treated group, CK7 was localized to the intercalated duct, striated duct, granular and excretory duct cells. Ki67 was mainly expressed in these CK7-positive (CK7+) ductal cells, and a small number of Ki67-positive cells (Ki67+) were located in non-ductal tissues.…”
Section: Parasympathetic Innervation Increases Ductal Epithelial Cell Proliferationmentioning
confidence: 98%
“…Ki67 and PCNA proteins are markers of cell proliferation, and CK7 is the marker of salivary ductal cells, respectively. 27,28 In the non-treated group, CK7 was localized to the intercalated duct, striated duct, granular and excretory duct cells. Ki67 was mainly expressed in these CK7-positive (CK7+) ductal cells, and a small number of Ki67-positive cells (Ki67+) were located in non-ductal tissues.…”
Section: Parasympathetic Innervation Increases Ductal Epithelial Cell Proliferationmentioning
confidence: 98%
“…The importance of β1 integrin in salivary epithelial branching morphogenesis has been established via antibody blocking experiments (Wei et al 2007). β1 integrin has also been shown to mediate the assembly of human salivary stem/progenitor microstructures by siRNA-mediated knock down (Wu et al 2019). Our results in this study provide genetic perturbation evidence that strengthens the finding that β1 integrin is required for branching morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Because cellular secretion of ECM proteins is minimal, hS/PCs engage with the synthetic matrix via immobilized cell-adhesive peptides. It has been shown that integrin-β1 is important for salivary gland development and the assembly of multicellular salivary gland spheroids. While receptors such as CD44, RHAMM, and ICAM can bind the HA matrix, the bioactive peptides are reported to target multiple isoforms of integrin-β1 . The RGDSP peptide predominantly ligates α 5 β 1 and α v β 3 integrin subunits. , The laminin-derived peptides, YIGSR and IKVAV, interact to varying extents with α 3 β 1 , α 4 β 1 , and α 6 β 1 . ,, YIGSR also has an affinity for a 67 kDa laminin receptor, to which much of its biological activity has been attributed. , Derived from perlecan domain IV, TWSKV is reported to primarily target a nonintegrin receptor, with limited integrin-β1 affinity. , While all 3D cultures were stained positive for integrin-β1, more pronounced staining was found on the larger spheroids localized to the basal domains.…”
Section: Discussionmentioning
confidence: 99%